Predicting treatment response in depression: the role of anterior cingulate cortex - Godlewska, BR; Browning, M; Norbury, R; Igoumenou, A; Cowen, P; Harmer, C (Oxford University Press, 2018)
Background: Identification of biomarkers predicting therapeutic outcome to antidepressant treatment is one of the most important tasks in current research because it may transform the lengthy process of finding the right treatment for a given individual with depression. In the current study we explored the potential of pre-treatment pregenual anterior cingulate cortex (pgACC) activity as a putative biomarker of treatment response. Methods: Thirty-two medication-free patients with depression were treated for 6 weeks with a selective serotonin reuptake inhibitor, escitalopram. Before treatment began, patients underwent an fMRI scan testing response to brief, masked, presentations of facial expression depicting sadness and happiness. Results: After 6 weeks of treatment there were 20 SSRI responders and 12 non-responders. Increased pre-treatment pgACC activity to sad versus happy faces was observed in responders relative to non-responders. A leave one out analysis suggested that activity in the ACC was able to predict response status at the level of the individual participant. Conclusions: The study supports the notion of pgACC as a promising predictor of antidepressant response.